Novel classification system and high-risk categories of pediatric acute myeloid leukemia - Umeda, Masayuki; Liu, Yen-Chun; Karol, Seth E.; Klco, Jeffery M. (Haematologica (Roma), 2025)
The prognosis of pediatric acute myeloid leukemia (AML) remains poor compared with pediatric acute lymphoblastic leukemia (ALL); accurate diagnosis and treatment strategies based on the genomic background are strongly needed. Recent advances in sequencing technologies have identified novel pediatric AML subtypes, including BCL11B structural variants and UBTF tandem duplications (UBTF-TD), associated with poor prognosis. In contrast, these novel subtypes do not fit into the diagnostic systems for AML of the 5th edition WHO classification or International Consensus Classifications (ICC) released in 2022. In this review, we describe the current state of pediatric AML classification in the context of a new classification framework based on the findings of updated genomic profiling. Molecular categories in the new classification system are associated with unique transcriptional, mutational, and clinical characteristics, which can be leveraged for predicting clinical outcomes and developing molecular-target therapies based on the initiating driver alterations. We also highlight four high-risk subtypes of pediatric AML, namely CBFA2T3::GLIS2, BCL11B, UBTF-TD, and ETS family fusions, focusing on their disease mechanisms, clinical associations, and possible therapeutic strategies to overcome the dismal clinical outcomes associated with these alterations.